The Role of the Islamic Student Association (HMI) in Shaping Student Leadership Character in the Digital Age - Predi Arda Saputra; Nuscarav Al Hariri (Journal of Pedagogi, 2025)
Digital transformation has significantly reshaped patterns of interaction and leadership within student organizations, including the Islamic Student Association (HMI). Students today must demonstrate not only intellectual competence but also adaptive and value-oriented leadership character. This study analyzes the role of HMI in shaping student leadership character in the digital era by applying Bernard M. Bass’s transformational leadership theory and Thomas Lickona’s character education framework. A literature review method was used, examining leadership theories, character formation, digital leadership, and HMI’s cadre development structure. The findings indicate that HMI’s cadre system aligns with transformational leadership principles and character-building approaches while demonstrating adaptability to digital-era demands through hybrid training models, digital literacy programs, and an expanded digital ecosystem. This study concludes that integrating Islamic values, national identity, and digital competence is essential for preparing visionary, ethical, and adaptive young leaders.